Distributed system of protection and diagnostics of support structural elements of high-voltage power lines - Breydo, Iosiv V.; Kaverin, Vladimir V.; Ivanov, Valeriy A.; Voytkevich, Sofiya V.; Levin, Igor V. (EAI Endorsed Transactions on Energy Web, 2017)
A distributed system of protection and diagnostics of support structural elements of high-voltage power lines (HVPL) on 500 kV voltage was developed at Karaganda State technical university: - current monitoring of leakage currents of bunches of suspension insulators; - detection ice-rime depositions; - cathode protection of underground elements of support constructions; - information transfer from the sensors placed on supports on the control office on telemetric channels; - creation of the passport of each support on SCADA – system basis. The system contains set of local subsystems constructively placed on the HVPL support, telemetry subsystem providing processing and information transfer from the sensors placed on support, a subsystem of processing and information storage on the control offices of different level. Power supply of local subsystems is provided from the directed energy of electromagnetic fields. The local subsystem consists of three identical, hybrid sensors of a leakage current of suspension insulators, Ice-rime depositions detection is carried out by the indirect methods based on the current monitoring of support reaction to wind and ice loads, and also temperatures and air humidity. Information from sensors allows to control the integral values of a leakage current of the industrial frequency and surface currents of the partial discharges proceeding through insulators bunches, and also to define the time point which is optimum for ice-rime depositions. Radio modem, cellular, and also satellite communication with an automatic channels choice of communication in the conditions of the powerful electromagnetic fields having significant effect on an opportunity and transmission quality of information is used for telemetric information transmission to the control office The passport of each controlled section support of HVPL which has the information archive on technical elements condition of HVPL construction support, trends of leakage currents, about the current alert conditions with localization of the place, time and a type of an alert condition was created in the control office.